Financial Policy Models: Theory and Practice - Carleton, Willard T.; Dick, Charles L.; Downes, David H. (Journal of Financial and Quantitative Analysis, 1973)
Intelligent corporate financial planning has been necessary for as long as the corporate form of business enterprise has existed. Only in recent years, however, have computer technology and academic theorizing been harnessed to meet this practical need. Without wishing to minimize the impact and value of these efforts on the practice of corporate finance, we do think there are grounds for believing that the new finance “tools” have been less than maximally effective. In this article we contrast typical financial modeling theory in order to interpret the gap between the two. Then we describe a financial policy model whose characteristics might be expected to be more acceptable in practice. Finally, we discuss the implications of the theory/practice gap and our experience with this model for future scholarly activities in the modeling of financial policies.